Front Cover: Covalent Immobilization of Naringinase over Two‐Dimensional 2D Zeolites and its Applications in a Continuous Process to Produce Citrus Flavonoids and for Debittering of Juices (ChemCatChem 18/2020). Issue 18 (18th September 2020) - Carceller, Jose Miguel; Martínez Galán, Julián Paul; Monti, Rubens; Bassan, Juliana Cristina; Filice, Marco; Yu, Jihong; Climent, María J.; Iborra, Sara; Corma, Avelino
Abstract : The Front Cover shows that the supported enzyme naringinase on a laminar zeolite is able to produce citrus flavonoids of important pharmacologic activities from citrus wastes, and in addition, the same enzymatic catalytic system is used for debittering citrus juices. In their Communication, J. M. Carceller et al. explain that naringine, a glycoside flavonoid abundant in citrus wastes, can be hydrolyzed selectively into the citrus flavonoids prunin and naringenin using the enzyme naringinase covalently immobilized on the pure silica zeolite ITQ‐2 with high efficacy. Additionally, the bitter taste of citrus juices produced by the presence naringine can be adjusted by treating the juice with the same catalytic system in a continuous flow process.More information can be found in the Communication by J. M. Carceller et al. .